Incidence of cancer and related deaths in hemoglobinopathies: A follow‐up of 4631 patients between 1970 and 2021. Issue 1 (2nd November 2022) - Origa, Raffaella; Gianesin, Barbara; Longo, Filomena; Di Maggio, Rosario; Cassinerio, Elena; Gamberini, Maria Rita; Pinto, Valeria Maria; Quarta, Antonella; Casale, Maddalena; La Nasa, Giorgio; Caocci, Giovanni; Piroddi, Antonio; et al.
Abstract: Background: The correlation between thalassemia and malignancies other than hepatocellular carcinoma (HCC) and the possible relationship between other hemoglobinopathies and tumor risk have been poorly evaluated. Methods: Eight Italian specialized centers evaluated the incidence of malignant neoplasms in hemoglobinopathies as well as their sites and features. The study cohort included 4631 patients followed between 1970 and 2021 (transfusion‐dependent β‐thalassemia, 55.6%; non–transfusion‐dependent thalassemia, 17.7%; sickle cell disease, 17.6%; hemoglobin H disease, 8.3%). Results: A total of 197 diagnoses of cancer were reported (incidence rate, 442 cases per 100, 000 person‐years). The liver was the most frequent site of tumors in both sexes, with a higher incidence (190 cases per 100, 000 person‐years) in comparison with the general population found in all types of hemoglobinopathies (except hemoglobin H disease). In recent years, tumors have become the second cause of death in patients with transfusion‐dependent thalassemia. A lower risk of breast and prostate cancer was observed in the whole group of patients with hemoglobinopathies. The first cancer diagnoses dated back to the 1980s, and the incidence rate sharply increased after the 2000s. However, although the incidence rate of cancers of all sites but the liver continued to show an increasing trend, the incidence of HCC showed stability. Conclusions: These findings provide novel insights into the relationship between cancer and hemoglobinopathies and suggest that the overall risk is not increased in these patients. HCC has been confirmed as the most frequent tumor, but advances in chelation and the drugs that have led to the eradication of hepatitis C may explain the recent steadiness in the number of diagnoses that is reported here. Abstract : Except for hepatocellular carcinoma, cancers are not more frequent in patients with hemoglobinopathies in comparison with the general Italian population. The incidence of hepatocellular carcinoma over time showed an increasing trend until 2012; since then, there has been a steady number of new diagnoses despite the increasing age of patients with hemoglobinopathies.